2021
DOI: 10.1177/1071100720983811
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Head Allografts for Talar Body Defects

Abstract: Background: Large structural bone deficits after a failed ankle arthroplasty or avascular necrosis (AVN) of the talus present a complex reconstruction challenge. The aim of this study was to report the results of patients undergoing an ankle arthrodesis or tibiotalocalcaneal fusion using a femoral head allograft (FHA). Methods: All ankle and tibiotalocalcaneal fusions using FHA between February 2006 and January 2019 were included. Forty-four patients (45 ankles) with a mean follow-up of 42.8 months were studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Both PROMIS and FFI data revealed mild to moderate pain and dysfunction at minimum 1-year follow-up. These findings were similar to those reported by Coetzee et al 10 Given this population’s disease severity, comorbidity profile, and limited alternatives for limb salvage, complete restoration of physiologic ankle function is not to be expected, particularly following fusion of the tibiotalar and subtalar joints. 40 Rather, preservation of a viable lower extremity is, in itself, a major endpoint.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Both PROMIS and FFI data revealed mild to moderate pain and dysfunction at minimum 1-year follow-up. These findings were similar to those reported by Coetzee et al 10 Given this population’s disease severity, comorbidity profile, and limited alternatives for limb salvage, complete restoration of physiologic ankle function is not to be expected, particularly following fusion of the tibiotalar and subtalar joints. 40 Rather, preservation of a viable lower extremity is, in itself, a major endpoint.…”
Section: Discussionsupporting
confidence: 89%
“…Very recently, Coetzee et al 10 reported a similarly high union rate of 90.7% in a retrospective cohort of 44 patients, with a mean follow-up of 42.8 months, who underwent tibiotalar or TTC arthrodesis with femoral head allograft for failed total ankle arthroplasty or talar avascular necrosis. They describe a unique transfibular approach to TTC arthrodesis with fibulectomy, meticulous cup and cone reamer preparation of congruent allograft surfaces, rigid internal fixation, and bridge grafting, which they attribute to the high rates of fusion.…”
Section: Discussionmentioning
confidence: 95%
“…The efficacy and effectiveness of bone allograft use have been confirmed [ 25 , 26 ]. Coetzee et al reported a case series of 44 patients with large talar body defects (after a failed ankle arthroplasty or avascular necrosis) undergoing ankle arthrodesis or tibio-talo-calcaneal fusion by using femoral head allografts [ 27 ]. The overall satisfaction rate was 78.6%, with 90.7% of ankles exhibiting favorable fusion at an average of 18.7 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, one patient underwent a below-the-knee amputation (BKA) after a healed TTC fusion because of persistent pain. 7 Additive manufacturing is the ability to down-lay material to create a 3-dimensional (3D) structure of any shape using numerous different materials. Three-dimensional titanium cages have been used to fill defects in the spine and acetabulum for many years, but more recently there has come the ability to custom print these cages to patient-specific needs.…”
Section: Introductionmentioning
confidence: 99%